109 Caprini Risk Score is Shockingly High in Penile Prosthesis Surgery Patients. Issue 1 (1st April 2022) - Habashy, E; Hebert, K; Helo, S; Ziegelmann, M; Collins, S; Trost, L; Kohler, T
ABSTRACT: Introduction: The significant overlap of risk factors for erectile dysfunction and venous thromboembolism (VTE) may disproportionally increase the risk of VTE in men undergoing inflatable penile prosthesis (IPP) surgery. Owing to the absence of available literature, AUA and EAU perioperative VTE guidelines do not address VTE risk with IPP surgery and generally recommend against pharmacologic prophylaxis with outpatient surgery. The Caprini Score is a validated scoring system to estimate VTE risk in the perioperative period. Objective: We sought to assess the risk of VTE by calculating Caprini Scores in men undergoing IPP surgery. Methods: We retrospectively reviewed and calculated Caprini Scores for patients undergoing IPP surgery at our institution between July 2017 and June 2019. Results: 215 patients undergoing IPP surgery were identified with a mean and median Caprini score of 5.96 (SD, 1.63) and 6 (IQR 5, 7), respectively. 84% of the cohort was classified as high or highest risk for VTE (Figure 1). This is in part due to our cohort's mean age of 64, mean BMI of 31 and history of prostate cancer treatment as the cause of ED. Prior history of VTE (deep vein thrombosis(DVT) or pulmonary embolism (PE)was identified in 17 (8%) patients with 5 (2%) have a history of both DVT and PE. Conclusions: Men undergoing IPP surgery are high risk for VTE based on Caprini score assessment. VTE prophylaxis should be considered in men undergoing penile implant surgery. Before widespread application, long-term data is necessary to assess safety and efficacy of VTE prophylaxis in the IPP surgery population. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Senior author consultant for Coloplast